Metal Industry Waste at Pesarean Village Tegal Regency: Analysis Impact and Potential as Supplement Science Learning - Arfiani, Y.; Rahayuningsih, M.; Marianti, A.; Nugraheni, A. R. E. (Universitas Negeri Yogyakarta, 2024)
This research aims to explore the impact of open burning and dumping on the local metal industry, analyze policies and their implementation regarding these practices, and utilize this pollution issue in learning. Using documentation techniques, interviews, literature studies, and secondary data, the study reveals significant environmental impacts, including air, soil, and water pollution, as well as health risks to the community. The findings of this research are that the problem of metal pollution in Pesarean Village can be included as a complement to environmental physics learning on several materials, namely the environment of water, land, air, pollution, and global warming. Two main impacts are identified: open burning releases harmful gases and particulate matter, leading to respiratory illnesses among workers and residents, while open dumping contaminates soil and groundwater, posing risks to human health and the environment. The government of Tegal Regency has implemented relocation and remediation policies to address these issues. However, challenges such as community resistance and resource constraints hinder policy implementation. The study suggests that the case of Pesarean's metal industry could serve as supplementary learning material for Environmental Physics courses at the university level. By integrating this real-world case into the curriculum, students can better understand environmental issues and develop critical thinking skills to propose effective solutions.